2020
DOI: 10.1007/s10668-020-00676-3
|View full text |Cite
|
Sign up to set email alerts
|

Powering and puzzling: climate change adaptation policies in Bangladesh and India

Abstract: South Asia is a region uniquely vulnerable to climate-related impacts. Climate change adaptation in India and Bangladesh evolves using powering and puzzling approaches by policy actors. We seek to answer the question: how do powering and puzzling approaches influence the climate change adaptation policy design and implementation processes in Bangladesh and India? We adopted two strategies to collect and analyze data: semistructured interviews and discourse analysis. We found that adaptation policymaking is lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 87 publications
(112 reference statements)
0
6
0
Order By: Relevance
“…Araos et al (2017) and Haque et al (2017) found that certain organizations encapsulate decision‐making power which leads to less collaborative efforts. Because of historical trends of preference for technical solutions over more integrated ones, the engineering or technical organizations do not feel compelled to cooperate with other organizations (Stock, Vij, & Ishtiaque, 2020). For instance, in an adaptation project in northeastern Bangladesh, the water board decided to construct river embankments for flooding ( I : interactions among national level actors ) without consulting with organizations involved in socio‐economic aspects of the area ( M : enclosure and exclusion ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Araos et al (2017) and Haque et al (2017) found that certain organizations encapsulate decision‐making power which leads to less collaborative efforts. Because of historical trends of preference for technical solutions over more integrated ones, the engineering or technical organizations do not feel compelled to cooperate with other organizations (Stock, Vij, & Ishtiaque, 2020). For instance, in an adaptation project in northeastern Bangladesh, the water board decided to construct river embankments for flooding ( I : interactions among national level actors ) without consulting with organizations involved in socio‐economic aspects of the area ( M : enclosure and exclusion ).…”
Section: Resultsmentioning
confidence: 99%
“…Bangladesh deals with a variety of climate adaptation issues, yet explanations of the causal mechanisms of barriers to adaptation are limited. For instance, various scholars such as Bhuiyan (2015), Paprocki and Huq (2018), Sovacool, Tan‐Mullins, Ockwell, and Newell (2017), Stock et al (2020), Sultana (2014), and Vij, Warner, Biesbroek, and Groot (2019) discuss the role power dynamics and interplay in Bangladeshi adaptation governance but there is a little to no explanation of how these power‐related issues become barriers. Our study advances the knowledge on barriers and their mechanisms in Bangladesh by providing a typology of common barrier mechanisms to climate adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…PQs on mitigation seemed to be more techno-managerial in focus, seeking to understand energy and agricultural policies, for instance-part of a larger trend that has been noted by other researchers in South Asia (Stock et al 2021).…”
Section: Climate Impacts Mitigation and Adaptationmentioning
confidence: 90%
“…Mikulewicz (2020) argues that successful alliances hinge on shared political indignations and deliberate attempts to undo constructed boundaries between state modalities, institutions, and those relegated to the peripheries of adaptation processes. Through commitment to robust partnerships that harness determination, radical approaches to (re)negotiating power can be ignited and sustained (Stock et al, 2020; Tschakert et al, 2016; Ziervogel, 2019).…”
Section: Utilising An Intersectional Subjectivities Lens For Moving T...mentioning
confidence: 99%